Acupuncture and clomiphene citrate for anovulatory infertility: a systematic review and meta-analysis. Issue 1 (February 2020) - Gao, Ranran; Guo, Baojun; Bai, Jun; Wu, Yeke; Wu, Keming
Objective: To evaluate the comparative effectiveness of acupuncture or acupuncture combined with clomiphene citrate (CC) versus CC alone on the outcomes of anovulatory infertility. Methods: A literature search in eight databases yielded nine randomised controlled trials (RCTs) that evaluated the comparative effectiveness of acupuncture and CC in anovulatory infertility. Subsequently, data were extracted and the studies were assessed for the quality of their methodological designs and risk of bias. Meta-analyses of the RCT data were conducted. Results: Nine trials including 1441 women were included in the meta-analysis. There were no significant differences in the rates of pregnancy (odds ratio (OR) 1.18, 95% CI 0.83 to 1.69), ovulation (OR 2.57, 95% CI 0.59 to 11.29) or pregnancy loss (OR 0.98, 95% CI 0.59 to 1.63) when acupuncture was used as an adjuvant therapy alongside CC. Although acupuncture alone did not increase the ovulation rate (OR 0.41, 95% CI 0.11 to 1.49), our review demonstrated superior effects in patients who received acupuncture as a separate treatment modality with respect to both the pregnancy rate (OR 2.34, 95% CI 1.76 to 3.10) and the maximum follicular diameter (mean difference 0.50 mm, 95% CI 0.44 to 0.56 mm) when compared with CC alone. Statistical analysis also showed a reduction in the rate of pregnancy loss when acupuncture was used as a separate treatment compared with CC alone (OR 0.19, 95% CI 0.08 to 0.45). Conclusions: Based on the above pooled results of the studies, the use of acupuncture as a monotherapy significantly improved the rate of pregnancy among the study participants compared with the use of CC alone. However, any results drawn from these studies should be interpreted with caution when considering the context of clinical practice.